2011
DOI: 10.1007/s00726-011-1127-4
|View full text |Cite
|
Sign up to set email alerts
|

Expression of transglutaminase-2 isoforms in normal human tissues and cancer cell lines: dysregulation of alternative splicing in cancer

Abstract: The multiple enzymatic activities and functions of transglutaminase type 2 (TG2) may be attributed to alternative TG2 molecules produced by differential splicing of TG2 mRNA. Different RNA transcripts of the human TG2 gene (TGM2) have been identified, but the expression of TG2 multiple transcripts has never been systematically addressed. We have confirmed and rationalized the main TG2 variants and developed a screening assay for the detection of alternative splicing of TG2, based on real-time reverse-transcrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(56 citation statements)
references
References 33 publications
2
54
0
Order By: Relevance
“…The expression levels of the constitutively spliced full-length TGM2-v1 and of four TGM2 variants ( TGM2-v2, v3, v4A, v4B ), generated by alternative splicing, 32 were evaluated by real-time PCR in mesothelium and MPM derived cell lines.…”
Section: Resultsmentioning
confidence: 99%
“…The expression levels of the constitutively spliced full-length TGM2-v1 and of four TGM2 variants ( TGM2-v2, v3, v4A, v4B ), generated by alternative splicing, 32 were evaluated by real-time PCR in mesothelium and MPM derived cell lines.…”
Section: Resultsmentioning
confidence: 99%
“…37 Previous work suggested that the short TGM2 form lacks the residual GTP-binding and carboxy-terminal portion necessary for recognition and binding to phospholipase C and is proapoptotic, whereas the long TGM2 form correlates more with increased cell survival. 23 Because the expression arrays used do not differentiate between the long and short TGM2 isoforms, we examined the expression of both isoforms in an independent and larger cohort, 128 EAC tumors, which also served as our validation cohort.…”
Section: Resultsmentioning
confidence: 99%
“…Because of the reported influence of TGM2 expression in various cancer cell lines on chemoresistance, 16,37 we examined TGM2 expression in a subset of 21 patients who had received preoperative chemotherapy, concurrent radiation therapy and subsequent esophagectomy, and whose tumors demonstrated minimal to no treatment response. TGM2 mRNA expression of this cohort was examined using qRT-PCR and compared with TGM2 expression from both normal esophagus (negative control) and EAC tumors with known TGM2 amplification (positive control) obtained from patients who had not received any chemotherapy or radiation therapy before operation.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies indicated that TG2 with its catalytic activity can incorporate polyamine in HPV18 E7 protein, thus inhibiting its binding to pRb protein in the cytosol and nucleus, thereby protecting the caspases degradation pathway [13,29,30]. In addition, recently, studies have shown that there is an increase in the splicing process of TG2 in dysplastic cells, indicating a relation between these TG2 molecules and the ones with intracellular cancer alterations [31].…”
Section: Discussionmentioning
confidence: 99%
“…These primers amplify E6 and E7 regions of the 38 most common HPV types. Nested PCR reaction was performed specifically with the types 45, 11,16,6,18,42,52,33,58,53,39,54,66,51,31,67,59, 62, 69, 35 e 68. All samples were analyzed by both the first reaction (PCR) and the second reaction (nested PCR).…”
Section: Hpv Typingmentioning
confidence: 99%